Exogenous melatonin delays oxidative browning in litchi during cold storage by regulating biochemical attributes and gene expression - Marak, Kilchira A.; Mir, Hidayatullah; Siddiqui, Mohammed Wasim; Singh, Preeti; Homa, Fozia; Alamri, Saud (Frontiers in Plant Science, 2024)
Oxidative damage leading to loss of nutritional quality and pericarp discoloration of harvested litchi fruits drastically limits consumer acceptance and marketability. In the present investigation, the impact of postharvestexogenous melatonin application at different concentrations i.e., (0.1 mM, 0.25 mM, and 0.5 mM,mM) ontreatment of litchi on fruits on quality and shelf life of litchi fruits under cold storage condition was studied. The results revealed the positive effect of melatonin at all concentrations on shelf life and fruit quality. However, 0.5 mM melatonin treatment efficiently minimized weight loss, decay loss, pericarp discoloration, and retained higher ascorbic acid, anthocyanin, antioxidant, and phenolics content till the end of storage period. Over theThroughout storage period, TSS, acidity, and total sugar of 0.5 mM melatonin treated fruits were retained higher level of TSS, acidity, and total sugar compared to the than other treatments. Melatonin administration also restricted the enzymatic eactivity of the polyphenol oxidase (PPO) and peroxidase PPO and (POD) enzymes in the fruit pericarp and maintained freshness of the fruits upto 30 days. At molecular level, a similar reduction in the expression of browning associated genes, LcPPO, LcPOD, and Laccase, was detected in preserved litchi fruits treated with melatonin. Anthocyanin biosynthetic genes, LcUFGT and LcDFR, on the other hand showed enhanced expression in melatonin treated fruits compared to untreated fruits. Melatonin treatment with 0.5 mM melatonin concentration could thus be beneficial for retaining fruit quality and avoiding pericarp browning of litchi fruits for up to 30 days in cold storage.